Association between teat-end hyperkeratosis and mastitis in dairy cows: A systematic review - Pantoja, J. C.F. [UNESP] (2020)
A systematic review was conducted to elucidate the role of teat-end hyperkeratosis (THK) as a risk factor for clinical mastitis (CM) or subclinical mastitis (SCM). Scientific papers on the subject were identified by means of a database search. All types of peer-reviewed analytical studies, observational or experimental and published in English, could be included in the review, regardless of publication year. Of 152 identified records, 18 articles were selected, of which 8 were prospective cohort studies, 9 were cross-sectional, and 1 was a hybrid case-control study. Internal validity of studies was assessed using a score system ranging from 0 to 6, based on design, risk of bias, and statistical methods. The most frequent study limitation was improper use of statistical methods to avoid confounding of associations between THK and CM or SCM. The 3 studies that used CM as outcome (all with high validity scores) showed positive associations with THK (especially severe), although the magnitude and statistical significance of the estimates differed among them. Most studies that used SCM as the primary outcome (based on microbiological examination of milk) reported that only severe THK was associated with SCM. Two studies with high validity scores reported moderate to strong associations between severe THK and incidence or prevalence of Staphylococcus aureus intramammary infection. Two studies with high validity scores reported that only severe THK was associated with the risk of somatic cell count (SCC) ≥200,000 cells/mL and increased mean SCC, respectively. Although 4 cross-sectional studies reported positive associations between THK and SCC, these associations were possibly spurious because confounding factors, such as parity, were not considered in the analyses. Results of the reviewed studies suggest that severe THK is a risk factor for both CM and SCM, as defined by microbiological examination of milk, SCC thresholds, or mean SCC. The effect of severe THK on both contagious (especially Staphylococcus aureus) and environmental CM or SCM emphasizes the importance of teat health for mastitis control. Four studies demonstrated that quarters with mild THK had lower prevalence of intramammary infection or lower mean SCC than quarters with no THK, suggesting that development of mild THK, as a physiological response to milking, can have a protective effect. Dairy consultants should focus on monitoring and minimizing occurrence of severe THK to prevent CM and SCM.